Pendampingan Remaja dalam Menghadapi Dampak Minuman Keras di Desa Jontlak Praya Tengah - Wirahadi, Pandu; Rahman, Alfian; Hariani, Afifah; Hamdu, Mustafa (Lembaga Publikasi Ilmiah Nusantara, 2025)
This community service initiative aims to raise awareness among teenagers about the negative impacts of alcoholic beverages through an educational and participatory approach in Jontlak Village, Central Praya. The implementation method includes preparation, awareness campaigns, and evaluation stages. The awareness campaign is conducted through interactive discussions, educational video screenings, and the distribution of informative brochures, involving teenagers, parents, and local community leaders. Evaluation results indicate a significant improvement in teenagers' understanding, as reflected in the average pre-test score of 42.3, which increased to 81.7 in the post-test. Participants responded positively to the educational media used and initiated discussion groups as a follow-up to the activity. Additionally, the involvement of families and the community played a crucial role in strengthening the program’s success, leading to the village’s commitment to continuing the program sustainably. This initiative makes a tangible contribution to building collective awareness and fostering a social environment that supports a healthy lifestyle among teenagers. Moreover, this community service model can be replicated in other regions as a community-based preventive strategy against alcohol abuse.